Odpowiedź :
a.
x+1 = 5 / -1
x = 4
b .
2x-3 = 4 / +3
2x = 7 / ;2x
x = 3,5
c.
c)- 3x= 1 - 7 / - 3
x= 2
d.
----
x+1 = 5 / -1
x = 4
b .
2x-3 = 4 / +3
2x = 7 / ;2x
x = 3,5
c.
c)- 3x= 1 - 7 / - 3
x= 2
d.
----
a) x= 5-1
x=4
b) 2x= 4+3
2x= 7 /2
x= 7/2
c)- 3x= 1-7 / (-3)
x= 2
d)5x= 0-1 /5
x= 0
x=4
b) 2x= 4+3
2x= 7 /2
x= 7/2
c)- 3x= 1-7 / (-3)
x= 2
d)5x= 0-1 /5
x= 0
a)
|x+1|=5
x+1=5
x=5-1
x=4
b)
|2x-3|=4
2x-3=4
2x=4+3
2x=7 [/:2
x=3,5
c)
|7-3x|=1
7-3x=1
7-1=3x
3x=6[/:3]
x=2
d)
|5x+1|=0
5x+1=0
5x=-1[/:5]
x=-1/5
:)
|x+1|=5
x+1=5
x=5-1
x=4
b)
|2x-3|=4
2x-3=4
2x=4+3
2x=7 [/:2
x=3,5
c)
|7-3x|=1
7-3x=1
7-1=3x
3x=6[/:3]
x=2
d)
|5x+1|=0
5x+1=0
5x=-1[/:5]
x=-1/5
:)